Molecular population genetics and phylogeographic studies of Ligia exotica and Ligia cinerascens in East Asia - Kim, Gyeongmin; Kim, Hyemin; Mun, Sohyun; Choi, Eun Hwa; Nguyen, Anh D.; Hwang, Ui Wook (Frontiers in Marine Science, 2023)
Introduction Sea slater, in the genus Ligia, is widespread in rocky shore habitats, and the taxon is easily isolated due to its limited dispersal capacity. Therefore, most Ligia species exhibit an allopatric distribution, but Ligia exotica and L. cinerascens exhibit an overlapping distribution distribution in East Asia. Previous studies on both species have confirmed the existence of highly divergent lineages based on 16S rRNA. Methods In the present study, 282 Ligia individuals were collected at ten, three, and three sites in South Korea, Japan, and Vietnam, respectively, and 41 haplotypes were observed based on 16S rRNA. Results and discussion The results of phylogeny, phylogenetic network, and TCS network, Principal Coordinates Analysis, and four Molecular Species Delimitation Analyses revealed that six genetic lineages including L. cinerascens, Lineages N and S of L. exotica, Ligia sp. 1, sp.2 and sp.3 were present. The three genetic lineages, including L. cinerascens, Lineage N of L. exotica, and Lineage S of L. exotica, were also identified in the phylogeny based on a nuclear gene of the sodium–potassium ATPase α-subunit (Nak). Phylogeographic analysis revealed that L. cinerascens and Lineage N of L. exotica were distributed overlappingly in South Korea, Japan, and the northern region of China. Generally, the two lineages of L. exotica were distributed allopatrically, which was more evident along the coastline of mainland China than that of Japan. The results of time-calibrated phylogeny suggested that the speciation events of Ligia species might be associated with Japanese mainland formation from Oligocene to Miocene (approximately 30-5 million years ago, Mya). The results of the present study provide insights that could facilitate the understanding of the evolutionary history of Ligia, tracking of geological processes, and evolutionary effects of palaeogeographical events at the population level.